Deposition and Characterization of Innovative Bulk Heterojunction Films Based on CuBi2O4 Nanoparticles and Poly(3,4 ethylene dioxythiophene):Poly(4-styrene sulfonate) Matrix - María Elena Sánchez-Vergara; América R. Vázquez-Olmos; Leon Hamui; Alejandro Rubiales-Martínez; Ana L. Fernández-Osorio; María Esther Mata-Zamora (Applied Sciences, 2021)
This work presents the deposition and study of the semiconductor behavior of CuBi2O4 nanoparticles (NPs) with an average crystallite size of 24 ± 2 nm embedded in poly(3,4 ethylene dioxythiophene):poly(4-styrene sulfonate) (PEDOT:PSS) films. The CuBi2O4 NP bandgap was estimated at 1.7 eV, while for the composite film, it was estimated at 2.1 eV, due to PEDOT:PSS and the heterojunction between the polymer and the NPs. The charge transport of the glass/ITO/PEDOT:PSS-CuBi2O4 NP/Ag system was studied under light and dark conditions by means of current–voltage (I–V) characteristic curves. In natural-light conditions, the CuBi2O4 NPs presented electric behavior characterized by three different mechanisms: at low voltages, the behavior follows Ohm’s law; when the voltage increases, charge transport occurs by diffusion between the NP–polymer interfaces; and at higher voltages, it occurs due to the current being dominated by the saturation region. Due to their crystalline structure, their low bandgap in films and the feasibility of integrating them as components in composite films with PEDOT:PSS, CuBi2O4 NPs can be used as parts in optoelectronic devices.